Association of CYP17 and MTRR Gene Polymorphisms with Clinicopathological Features of Breast Cancer Patients (Global Journal of Medical Research, 2020)
Allele frequencies of T-34C CYP17 and A66G MTRR polymorphisms in breast cancer samples and the correlation with clinicopathological data can contribute to the prognosis and knowledge of the genetic profile of a population. In this study, was analized the association of T-34C CYP17 and A66G MTRR polymorphisms with clinicopathological data in 82 samples of invasive ductal breast carcinoma in the Southwest region of Bahia. PCR-RFLP was used to determine the genotypes for A66G MTRR and T-34C CYP17 polymorphisms. The allele frequency was 0.369 and 0.631 for A66G MTRR; 0.672 and 0.328 for T-34C CYP17. The A66G MTRR genotypes showed deviation from Hardy-Weinberg equilibrium (p=0.000), the genotypes are not segregating independently (p=0.036). No association of polymorphisms with clinicopathological features was observed.
Keywords: Breast cancer; CYP17; MTRR; polymorphism